He Poroporoaki ki a Te Rere Amoamo (Monte) Ohia - Milroy, Wharehuia (Te Kaharoa, 2008)
This is a transcription of a poroporoaki, or farewell, for Monty Ohia, given by Professor Wharehuia Milroy. The transcription is by Jason King.